An easy-to-use prehospital severity scoring tool to triage COVID-19 positive adults in a resource-limited setting - Ali, Danish; Zubairi, Mustafa; Ayub, Maaha; Awan, Safia; Ali, Akbar Shoukat; Ali Bin Sarwar Zubairi (Journal of the Pakistan Medical Association, 2023)
Objective: To develop an easy-to-use severity scoring tool for prehospital triage of patients infected by the coronavirus disease-2019 in resource-limited settings. Method: The cohort study was conducted at a tertiary care hospital in Karachi, from August to September 2020, and comprised adult patients of either gender who tested positive for coronavirus disease-2019 on real-time polymerase chain reaction. The scoring system and categorisation were based on validated scales for the detection of pneumonia and opinions from pulmonologists. Data was analysed using SPSS 19. Results: Of the 206 participants, 100(48.5%) were in-patients and 106(51.5%) were out-patients. There were 144(69.9%) males and 62(30.1%) females with an overall mean age of 48.4±16.2 years. After categorisation based on severity, significantly higher number of in-patients were found to be in categories III and IV (p<0.05). Conclusion: The severity scoring tool could effectively help classify coronavirus disease-2019 patients into mild, moderate and severe cases. Key Words: Severity scoring tool, COVID-19 management, Pre-hospital triage, Low- and middle-income countries, Resource-limited setting.